2015
DOI: 10.1590/s0102-865020150100000002
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of bone repair in diabetic rats subjected to ƛ780 nm low-level laser therapy

Abstract: Brazil. Design of the study, histological examinations, manuscript writing, supervised all phases of the study. ABSTRACT PURPOSE:To investigate the effect of low-level laser therapy on bone healing in diabetic rats. METHODS:Bone cavities (19 mm diameter) were performed in the femur of 72 alloxan-induced diabetic rats, which were assigned into four groups: CTR (non-diabetic control), DBT (diabetic) CTRL (non-diabetic irradiated) and DBTL (diabetic irradiated). Low-level laser therapy was performed every 48h for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 26 publications
(24 reference statements)
3
4
0
Order By: Relevance
“…Low-level laser therapy provided a significant decrease in the severity of the inflammatory response in the late phases of wound healing independent of the protocol used. Supporting our findings, similar results have also been reported in the literature (15)(16)(17).…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Low-level laser therapy provided a significant decrease in the severity of the inflammatory response in the late phases of wound healing independent of the protocol used. Supporting our findings, similar results have also been reported in the literature (15)(16)(17).…”
Section: Discussionsupporting
confidence: 94%
“…Paradoxically, Pereira et al (19) have observed that LLLT in the red spectrum promotes a significant increase in mast cell degranulation in the first 24 h after tissue aggression, generating a transient amplification of the acute inflammatory response, followed by a substantial reduction in neutrophil content after 36 h. These data seem to suggest that LLLT modulates the inflammatory response in order to accelerate the acute phase and thus culminate in the anticipation of process chronification. Although the precise mechanisms underlying the modulatory effects of LLLT on the inflammatory response were not investigated in the current paper, it is possible to suggest that it might be related to the inhibitory effect of laser energy on the release of pro-inflammatory chemical mediators, such as TNF-α, IL-1β and IL-6, as previously described (15). However, further investigations are still necessary to attest this hypothesis.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…In our study, we found that the induction with the alloxan was effective in the development of experimental diabetes due to irreversible damage in beta cell, as found by Nascimento et al (2015), who used this drug and obtained similar results, being it an excellent experimental model.…”
Section: Discussionsupporting
confidence: 78%